Elaboración de un manual tipo para operación y mantenimiento de sistemas de agua potable en ciudades menores a 150 000 habitantes - Rosero Parra, Cesar Eduardo (2023)
There is a long journey that water has traveled from its source to our homes, known as the drinking water cycle, which is why these systems require crucial tasks such as operation and maintenance to function correctly and to ensure that the water supplied to the population is safe for consumption. The source of capture used is spring water that works by gravity and tends to be of good quality and with few contaminants. This manual is a detailed, complete and fully operational document that is easy to handle, understand, and execute and describes a drinking water system. The water source process has four components, including a sand remover. The distribution system, storage tank, and household connections have four components. On the other hand, the sewer lines are composed of five components, as are the basic recommendations. Finally, water treatment is a crucial stage consisting of six components responsible for removing contaminants and ensuring the water is safe for human consumption. Each component details, not only the necessary activities for the proper functioning of the drinking water system but also the frequency and time required for each one, allowing for establishing performance indicators for human resources. Likewise, each task's necessary materials and tools are specified, facilitating production preparation and purchasing budgets.